(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Radiation therapy is an effective cancer treatment option in conjunction with chemotherapy and surgery. Emerging individualized internal and systemic radiation treatment promises significant improvement in efficacy and reduction of normal tissue damage; however, it requires cancer cell targeting platforms for efficient delivery of radiation sources. With recent advances in nanoscience and nanotechnology, there is great interest in developing nanomaterials as multifunctional carriers to deliver therapeutic radioisotopes for tumor targeted radiation therapy, to monitor their delivery and tumor response to the treatment. This paper provides an overview on developing nanoparticles for carrying and delivering therapeutic radioisotopes for systemic radiation treatment. Topics discussed in the review include: selecting nanoparticles and radiotherapy isotopes, strategies for targeting nanoparticles to cancers, together with challenges and potential solutions for the in vivo delivery of nanoparticles. Some examples of using nanoparticle platforms for the delivery of therapeutic radioisotopes in preclinical studies of cancer treatment are also presented.